2009
DOI: 10.1056/nejmoa0806375
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss to Treat Urinary Incontinence in Overweight and Obese Women

Abstract: BACKGROUND-Obesity is an established and modifiable risk factor for urinary incontinence, but conclusive evidence for a beneficial effect of weight loss on urinary incontinence is lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
284
2
26

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 543 publications
(343 citation statements)
references
References 36 publications
18
284
2
26
Order By: Relevance
“…29 In our study, the increase in total testosterone was correlated with the magnitude of weight loss and reduction in WC, possibly because of reduced insulin resistance; 5,30 moreover, aromatase activity in adipose tissue results in increased estradiol production, decreased pituitary gonadotropin production and reduction in testicular synthesis of testosterone. 31 In obese women, urinary symptoms and incontinence are improved by weight loss, 32 but there is a paucity of similar data in men. To our knowledge, these are the first data to show that diet-induced weight loss ameliorates LUTS in obese men with undiagnosed urinary tract dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 In our study, the increase in total testosterone was correlated with the magnitude of weight loss and reduction in WC, possibly because of reduced insulin resistance; 5,30 moreover, aromatase activity in adipose tissue results in increased estradiol production, decreased pituitary gonadotropin production and reduction in testicular synthesis of testosterone. 31 In obese women, urinary symptoms and incontinence are improved by weight loss, 32 but there is a paucity of similar data in men. To our knowledge, these are the first data to show that diet-induced weight loss ameliorates LUTS in obese men with undiagnosed urinary tract dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The International Prostate Symptom Scale (IPSS) is a series of questions used to assess the severity of irritative (frequency, urgency, nocturia) and obstructive LUTSs (incomplete emptying, intermittency, weak stream, straining), attributable to bladder outlet obstruction caused by prostatic enlargement. 19 Symptoms are classified as mild (score 0-7), moderate (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) or severe (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Questionnairesmentioning
confidence: 99%
“…Three new RCTs were added; all report significant improvement in UI associated with weight loss. [4][5][6] Massive weight loss (15 to 20 BMI points) decreases UI in morbid obesity (Level of Evidence: 2). Moderate weight loss is effective in decreasing UI if combined with exercise.…”
Section: Urinary Incontinence (1a) Lifestyle Interventionsmentioning
confidence: 99%
“…A large randomized trial of overweight and obese women with urinary incontinence symptoms underwent an intensive 6 month weight loss program compared to a group with a structured education program. (Subak et al, 2009) Mean weight loss was 8 percent (7.8 kg) and 1.6 percent (1.5 kg) in the intervention and control groups, respectively. The authors found that weekly incontinence episodes decreased by 47 percent in the intervention group compared to only 28 percent in the control group.…”
Section: Dietary and Lifestyle Modificationmentioning
confidence: 88%